2001
DOI: 10.1007/bf02492244
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatographic enrichment ofN-acetylmethionine from casein hydrolysates for stable-isotope-ratio analysis of sulfur

Abstract: Key WardsColumn liquid chromatography Sulfur stable-isotope-ratio analysis Isotope-fractionation Casein N-Acetylmethionine SummaryA chromatographic method has been developed for enrichment of methionine-bouncl sulfur ~n casein, for stable-isotope analysis. Casein is precipitated from milk samples and cleaved by acid hydrolysis in 6 M hydrochloric acid at 95 ~ The amino acids released are converted into their N-acetyl derivatives by addition of acetic acid anhydride. After lyophihzation, N-ace@-methionine is se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Determination of δ 34 S was carried out on methionine separated from hydrolyzed casein according to the published protocols ( , ).…”
Section: Methodsmentioning
confidence: 99%
“…Determination of δ 34 S was carried out on methionine separated from hydrolyzed casein according to the published protocols ( , ).…”
Section: Methodsmentioning
confidence: 99%
“…The isocratic mobile phase was water-methanol (9:1, v/v). It was indicated that the method can be applied for the authenticity and traceability tests of dairy products containing casein (Lamprecht and Haberhauer, 2001).…”
Section: Reversed-phase Hplc Of Amino Acidsmentioning
confidence: 99%